ANALISIS KESALAHAN SISWA KELAS VIII SMP DI KOTA PADANG DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN KRITERIA WATSON - Novia Andiana (Jurnal Edukasi dan Penelitian Matematika, 2020)
One of the abilities that must be developed in learning mathematics is the ability to solve story problems. However, students have difficulty understanding math problems in the form of stories, so it is necessary to conduct a study to reveal the types of errors made by students and the factors that cause student errors in working on number pattern application questions with Watson's criteria. This type of research is a descriptive analytical study with a qualitative approach. The research subjects were students of class VIII totaling 21 students. After conducting the research, it was found that the types of errors that were often carried out by students were inappropriate procedures with a percentage of 26.99% and missing conclusions with a percentage of 34.13%. The causes of this error include students not being able to abstract data on the questions, students using incorrect formulas because they do not carefully read the questions, do not master the concept of number patterns, students forget to make conclusions because they think that the end of completion does not require conclusions, students lack skills regarding algebra and integer operations and students do not understand the problem. Keywords ─ Error Analysis, Watson’s Criteria